Integrated Aquifer Characterization in the Parowan Valley with Drillers' Logs and Transient Electromagnetic Systems - Bratzler, Kendra Danae, author; Smith, Ryan G., advisor; Bailey, Ryan, committee member; Stright, Lisa, committee member (Colorado State University. Libraries, 2026)
The Parowan Valley in southwestern Utah is an agricultural region that has experienced significant land subsidence in recent years due to excessive groundwater pumping. Subsidence occurs primarily in regions containing fine-grained materials such as clay deposits, making accurate characterization of subsurface lithology critical for informing groundwater management strategies aimed at mitigating further subsidence. Previous subsurface characterization efforts have relied on either geophysical data or directly sampled lithologic data independently. This study integrates both datasets to improve subsurface characterization within Parowan Valley. Transient electromagnetic (TEM) measurements collected using tTEM and WalkTEM systems provide spatially extensive electrical resistivity data and offer a faster, more cost-effective alternative to direct sampling methods. However, converting resistivity to lithology requires a rock physics transform and is strongly influenced by subsurface saturation conditions. To address this, monitoring well data were used to estimate depth to groundwater throughout the study area using cokriging with land surface elevation as a secondary variable. Direct lithologic observations were obtained from drillers’ logs, which provide subsurface material descriptions but are subject to inconsistencies due to an absence of standardized reporting practices. The geophysical and lithologic datasets were integrated and interpolated using ordinary kriging. Model performance was evaluated using held-out drillers’ logs to assess interpolation accuracy and optimize resistivity thresholds for saturated and unsaturated coarse-grained and fine-grained materials. Results demonstrate that integrating geophysical, lithologic, and hydrologic datasets improves subsurface characterization relative to interpolation performed using lithologic observations alone. The resulting interpolated fraction of coarse-grained material maps provide insight into the spatial distribution of clay deposits and may support groundwater management efforts in regions vulnerable to land subsidence.
Keywords: Groundwater; Rock physics transform; WalkTEM; Hydrogeophysics; Aquifer characterization; Transient electromagnetics